Determination of Agility in Elderly using Assistive Device by 8 Foot Up and Go Test - Ritu Chhabra; Manali Desai; Ajay Kumar (Journal of the Indian Academy of Geriatrics, 2018)
Background: With increasing age agility starts declining. Use of an assistive device hopefully aids in improving balance, agility, and confidence. There are fewer studies of objective quantification of agility with the use of the assistive device. This study aims to determine the agility in elderly using an assistive device by 8 foot up and go test. Methods: A comparative, experimental study was done on 60 Healthy adults of age 75 to 85 years. Subjects were asked to perform 8 foot up and go agility test initially without assistive device and then with an assistive device. The time in seconds was noted respectively. The mean of the two trials each was calculated. The data were analyzed using the paired t-test. Results: There was a statistically significant difference in mean agility score on 8 foot up and go test between subjects without an assistive device (12.33 ± 3.21 seconds) and with an assistive device (13.33 ± 3.39 seconds). Subjects when given assistive device took a longer time to complete the 8 foot up and go agility test than they required for completing it without an assistive device. Conclusion: There was a significant decrease in agility in elderly using an assistive device as shown by the increase in time taken to complete the 8 foot up and go agility test. There is a need for cautious clinical prescription practice for mobility aids.